Kajian Yuridis Pertanggungjawaban Pidana Terhadap Praktik Jual Beli Akun Ojek Online - Claudia Theophilia; Tantimin Tantimin (Universitas Serang Raya, 2022)
The digital economy is the part of the economy that enables and conducts trade in goods and services through electronic commerce on the Internet. It is also referred to as the internet economy or online economy, because many digital service providers use the internet to provide services to end users including online motorcycle taxis. The internet-based online motorcycle taxi business makes it easy for passengers who need transportation. With just one click on the smartphone and having the application of that system, then one can order a motorcycle taxis and taxis, even now, there are many new features, namely online food ordering and online services. However, in addition to the convenience, there is a practice of buying and selling accounts by drivers that can harm passengers. The purpose of this paper is to find out how the criminal liability for the practice of buying and selling motorcycle taxi accounts online. The research method conducted by the author is a qualitative normative research. The results show that the working relationship between the driver and the application provider is a mutually beneficial partnership relationship. The application provider prohibits account buying and selling transactions, thus the sanctions that can be given to perpetrators are suspension and breaking up of partners. Meanwhile, criminal liability by the perpetrator can be charged under Article 35 jo. Article 51 paragraph (1) of The Electronic Information and Transaction Law.